The development of Folk Science Lesson plans which concerned for Lanna Local wisdom in the psychotherapy for elderly - ใจเตี้ย, อาทิตยา (Community and Social Development Journal, 2017)
The purpose of this study was to develop and efficiency assessment of Folk Science Lesson plans which concerned for Lanna Local wisdom in the psychotherapy. 297 household, 12 elderly persons and 8 caregivers in the area of Suthep sub - district Municipality, Muang Chiangmai District, Chiangmai Province. Data were collected by using questionnaires, group discussion in-depth interview, and questionnaire before and after the Folk Science Lesson plans were Lanna Local wisdom in the psychotherapy had begun. The Folk Science Lesson plans prepared had efficiency of E1 / E2 according to the set criteria of 80/80, Means, Standard deviation, Paired t-test and content analysis were used for data analysis. The results indicated that the relationship aspect of Lanna Local wisdom in the psychotherapy was on the highest level (= 2.35). The Folk Science Lesson plans Lanna Local wisdom in the psychotherapy of elderly were 83.18 / 85.25 and caregivers 82.27 / 85.73 .The efficiency gain on each lessons were specified at 80.00 / 80.00 percent (E1 / E2). Comparison of Flok Science Lesson the post – learning achievement score was higher than the pre – learning score (P - value = 0.002, and 0.01).